Athens as Symbolic Space: Spatial Representations and the Conceptualization of the City through Narratives and Urban Plans - Demertzi, Aggeliki (Technical Annals, 2025)
This paper explores the dynamic interplay between urban narratives and spatial policies in shaping contemporary Athens' identity, tracing significant transformations from the early 2000s to the present. Drawing from Lefebvre’s representational spaces and Barthes’ myths, it illustrates how dominant narratives and spatial policies mutually construct and reshape each other, reflecting evolving political, economic, and social contexts.Initially, Athens' identity aligned with the global aspirations symbolized by the 2004 Olympic Games, projecting the city as an international metropolitan center. The subsequent Greek financial crisis radically altered these narratives, recasting Athens as a space of decline, unrest, and socio-political activism. Movements such as the "Indignants" protests transformed public spaces into symbolic arenas of resistance and cultural expression, reshaping global perceptions of the city. Since 2017, Athens experienced another narrative shift emphasizing cultural revival and increased touristification. International events like Documenta 14, and strategic media portrayals rebranded the city as resilient, creative, and culturally vibrant. These optimistic narratives, however, intensified urban inequalities and accelerated gentrification processes, highlighting tensions between symbolic representations and residents lived realities. Strategic urban planning practices under neoliberal governance reinforced these narratives, shifting from state-centered managerialism to entrepreneurial frameworks prioritizing investment attraction and commodification of urban spaces. Despite the proliferation of participatory initiatives, governance practices became increasingly fragmented and less democratic, sidelining genuine social equity, inclusion, and spatial justice.